Hubungan Pengetahuan dan Sikap Murid SD Kelas V dan VI dengan Kesiapan Menghadapi Menarche di SD Negeri 4 Kolakaasi Kecamatan Latambaga Kabupaten Kolaka: The Relationship between Knowledge and Attitudes of Grade V and VI Elementary School Students and Readiness in Facing Menarche in SD Negeri 4 Kolakaasi Latambaga District Kolaka Regency - Yuhanah, Yuhanah; Bangu, Bangu (Jurnal Surya Medika (JSM), 2020)
Menarche specifically refers to a woman's first menstruation during early adolescence (puerperal period) where the body growth (growth spurt) is very fast accompanied by hormonal changes that dramatically impact on increasing levels of reproductive function and all sexual maturation in the transition period, resulting in psychological changes, anxious children and symptoms of laziness to do something, especially in learning when the age of 10-14 years, the growth of sexual drive is a trigger for adolescent reproductive health problems is quite serious, making adolescents vulnerable to disease (STDs, HIV-AIDS) and teenage pregnancy great opportunity to have an abortion and narcotics. Adolescents in Indonesia number around 66.3 million people out of a total population of 258.7 million and one in four residents are teenagers. Southeast Sulawesi health profile data in 2017 the number of female population aged 10-14 years was 136,834 people (19.28%) while in Kolaka Regency, the female group aged 10-14 years amounted to 12,020 people (20.92%) of the total population of 251,520 souls. The purpose of this study was to analyze the relationship of knowledge and attitudes towards readiness to face menarche through a cross-sectional approach with the chi-square test. The research was carried out in February until May 2019 with the object of the research being female students of class V and VI at SDN 4 Kolakaasi Latambaga District, Kolaka with 50 respondents with a purposive sampling technique. The research results obtained that there was no relationship between knowledge and readiness of students facing menarche with a value of P = 0.46> α = 0.05 and there was no relationship between attitudes and student readiness in dealing with menarche with a value of P = 1,000> α = 0.05.